A novel design of a passive variable stiffness soft robotic gripper. (1st November 2022) - Shan, Yu; Zhao, Yanzhi; Pei, Changlei; Yu, Hongnian; Liu, Pengcheng
Abstract: Inspired by the twisting and hanging phenomenon of vines, this paper proposes and designs a passive variable stiffness soft robotic gripper to grasp an object in a simple and robust manner using the principle of jamming. This method has the characteristics of high reliability and good stability, which can achieve soft grasping and rigid load-bearing of the object. Firstly, according to two key issues, the design model of the gripper is proposed, the principle of the proposed gripper is analyzed, and the relationship between the stiffness of the gripper and the stiffness of the object is revealed. Secondly, the model of the robotic gripper is created using a conventional motor drive method, and the grasping process and deformation causes of the gripper are analyzed by using the principle of instability effect and large deformation principle. Finally, the experimental prototype is developed and the feasibility of the design principle and the grasping deformation process of the gripper are verified by gripping experiments.